THE QUALITY OF BUCKWHEAT GROATS IMPORTED TO UKRAINE - Kalashnyk, O. V.; Moroz, S. E.; Barabolia, O. V.; Remizova, N. L. (Scientific Progress & Innovations, 2019)
The highest social value recognized in Ukraine at the constitutional level is human life and health. The main factors of the population well-being include the quality and safety of food products. In this article, analytical and practical studies were conducted concerning the quality of buckwheat, a traditional food product in Ukraine. The object of the study was buckwheat produced by the LLC “Kolos” (Kazakhstan). Standard methods were used for measurements. The purpose of the research was to establish the level of buckwheat quality produced by the LLC “Kolos” (Kazakhstan), which is imported to Ukraine. To achieve this goal, the following tasks were solved: scientific papers, standard documents and regulatory-legal acts determining the requirements as to the quality of buckwheat were analyzed; the basic requirements concerning the quality of buckwheat were clarified; the program of studying buckwheat was made; packaging and labeling of buckwheat were analyzed; organoleptic, physical-chemical indices of buckwheat quality were investigated; the conclusions on the quality of the buckwheat produced by the LLC “Kolos” were formulated. During the research, it was found that the labeling of buckwheat did not contain the following property details: the production batch number and the bar code. This made it possible to establish that labeling of buckwheat produced by the LLC “Kolos” did not meet the requirements of normative documents. The investigation established the outward appearance (mainly unbroken buckwheat kernels, which do not pass through a sieve having 1.6 mm x 20 mm holes), the color (kernels of light brown color of different shades), the odor (a pleasant groat odor characteristic of buckwheat, no off-odors, no musty odor, no fust), flavor (pleasant groat taste, slightly nutty flavor, characteristic of buckwheat, without foreign flavors, not sour, not bitter). According to the results of the study, it was established that buckwheat, produced by the LLC “Kolos”, as to organoleptic parameters, meet the requirements of normative documents. As a result of the research, it was established that in the buckwheat sample, 99.7 % made good quality kernels, 0.2 %. made unshelled kernels. Concerning the physical-chemical indices of the quality of buckwheat imported to Ukraine, moisture content was determined – 13.5 % and the capacity of boiling soft – 15 minutes. These values corresponded to the requirements for No. 1 grade of peeled buckwheat according to the requirements of the normative documents.